Reliability of Different Protocols for Elbow Flexion and Extension Strength Measurement via Hand-held Dynamometer - Yeşilyaprak, Sevgi Sevi; Özden, Fatma; Karabay, Damla; Şahiner Pıçak, Gonca (Sportverletzung · Sportschaden, 2025)
To investigate the reliability of elbow flexion and extension strength measurements via a hand-held dynamometer (HHD) in different positions and to determine the minimal detectable change (MDC).Reliability study.Twenty healthy university students were evaluated at an exercise laboratory. Elbow flexion and extension strength were each measured by two physiotherapists in three different positions. Intra-class correlation coefficients (ICCs) were calculated to assess intra-rater reliability (ICC 3,3) and inter-rater reliability (ICC 3,3) and were used to calculate MDC.All measurement procedures have excellent intra- and inter-rater reliability scores in females (0.88–0.98) and males (0.81–0.95), except for moderate intra-rater reliability (0.72) for seated measurement of elbow flexion strength with the shoulder at 90-degree flexion in males. There is a systematic difference in inter-rater results for all flexion positions and intra-rater results for one flexion position in males (p<0.05). MDC95% ranged from 3.44 to 11.69 for intra-rater scores and from 6.19 to10.79 for inter-rater scores.All procedures showed excellent reliability, except for moderate intra-rater reliability in seated measurement of elbow flexion strength with the shoulder at 90-degree flexion in males. However, elbow flexion measurement was prone to systematic differences in males. Muscle strength of the tested individual and testers should be considered.
Keywords: physical fitness; healthy; evaluation study; musculoskeletal system